If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 73y = 36(2y + 11) Reorder the terms: 73y = 36(11 + 2y) 73y = (11 * 36 + 2y * 36) 73y = (396 + 72y) Solving 73y = 396 + 72y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-72y' to each side of the equation. 73y + -72y = 396 + 72y + -72y Combine like terms: 73y + -72y = 1y 1y = 396 + 72y + -72y Combine like terms: 72y + -72y = 0 1y = 396 + 0 1y = 396 Divide each side by '1'. y = 396 Simplifying y = 396
| 29y=14(2y+32) | | x+6/7=x+7/8 | | 299=14(2y+32) | | 14c-c-15c-(-20)=6 | | f(x)=x^3-5x^2+8x-40 | | -2x+4y=-7 | | -18v+10v-(-6v)=-16 | | -8x-4y=-44 | | 2w-6+w=6w-9 | | 8X^2+13x-28=2x^2-x | | -8x-4(-5)=-44 | | 5+2x=250 | | 15v-11v-(-17)=-11 | | x^2-25/4=0 | | 2/5*3/7 | | 0=-3Y+8X-9 | | 9x+16-8x=-5-10 | | 11(9c-1)-18=97c+11 | | -11g-(-12g)-7g-g=7 | | c^2-4c-16=4 | | 6(y-3)=4y-26 | | v/4-3=-9 | | 9x-4y=-14 | | 1-3x=19+6x | | 7x(x+2)+5=3x(x+1) | | 64v^2=36 | | 8x=7x-7 | | c^2-4c+16=4 | | -8-10=7x+18-6x | | -3+15=13x-4-12x | | -3x+2+4x=-17+16 | | 200/220= |